Mapping The Intellectual Structure of Service Quality and Customer Loyalty Research: A Global Bibliometric Study in The Banking Industry - Yanik Febriyani; Budi Eko Soetjipto; Madziatul Churiyah (PT. Maju Malaqbi Makkarana, 2026)
This study aims to map the intellectual structure and global research trends regarding service quality and customer loyalty in the banking industry through a Systematic Literature Review (SLR) and bibliometric analysis. Research data were obtained from the Scopus database covering the period from 2018 to 2025 using the keywords service quality, customer loyalty, and banking industry. The literature selection process was conducted using the PRISMA protocol, resulting in 33 scientific articles that met the inclusion criteria for further analysis. Bibliometric analysis was performed using VOSviewer software to map author collaboration networks, keyword relationships, and the evolution of research themes. The research findings indicate that the concepts of service quality, customer satisfaction, and customer loyalty are core themes dominating the research literature in the banking sector. Additionally, the study highlights the emergence of new themes related to customer experience, digital services, corporate social responsibility, and customer relationship management, which enrich the understanding of customer loyalty formation. Bibliometric visualizations also indicate that research collaboration remains relatively limited and scattered across several small groups of authors, despite the research having been reviewed on a global scale. These findings confirm that research on service quality and customer loyalty in the banking industry continues to evolve toward a more multidimensional approach in tandem with the ongoing digital transformation of services.